Life course approach to prevention and control of non-communicable diseases. (28th January 2019) - Mikkelsen, Bente; Williams, Julianne; Rakovac, Ivo; Wickramasinghe, Kremlin; Hennis, Anselm; Shin, Hai-Rim; Farmer, Mychelle; Weber, Martin; Berdzuli, Nino; Borges, Carina; Huber, Manfred; Breda, João
Abstract : A successful approach to reducing the burden of non-communicable disease requires action at all stages of life, argue Bente Mikkelsen and colleagues